Interkulturelle Bildung durch schulische Mehrsprachigkeit. Über die integrative Kraft von Türkisch in einem bilingualen Sprachenprogramm einer Grundschule in Hannover - Küppers, Almut 19XX- (Zeitschrift für Pädagogik und Theologie, 2016)
Intercultural communicative competency is solidly grounded in the foreign language subjects as the most important learning objective. The article argues that in immigrant societies migration induced multilingualism can be seen as an asset for both individuals and society alike. How multilingualism can be used as a source for the development of transnational capital is illustrated against the backdrop of an ethnographic case study. In the context of an elementary school in multi-ethnic Hanover, Turkish as the dominant community language in the neighborhood was integrated into the school curriculum as part of a bilingual programme, and, thus, upgraded. The findings indicate that such an unusual language programme not only contributes to achieving more educational justice but also opens up spaces for intercultural encounters and offers a place of belonging for the descendants of former immigrants.